2013
DOI: 10.1242/dev.092809
|View full text |Cite
|
Sign up to set email alerts
|

miR-200 and miR-96 families repress neural induction from human embryonic stem cells

Abstract: SUMMARYThe role of miRNAs in neuroectoderm specification is largely unknown. We screened miRNA profiles that are differentially changed when human embryonic stem cells (hESCs) were differentiated to neuroectodermal precursors (NEP), but not to epidermal (EPI) cells and found that two miRNA families, miR-200 and miR-96, were uniquely downregulated in the NEP cells. We confirmed zinc-finger E-box-binding homeobox (ZEB) transcription factors as a target of the miR-200 family members and identified paired box 6 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 48 publications
6
55
0
Order By: Relevance
“…miR-96 and miR-200 families are known to suppress neural differentiation by targeting key neural transcription factors PAX6 and ZEB1 [36]. Consistent with their upregulation (Supplementary information, Table S5), we observed that pax6 and zeb1 mRNAs were significantly downregulated in ADAR1 KD H9 cells upon differentiation (data not shown).…”
Section: Catalytically Inactive Adar1-e912a Rescues Retarded Neural Isupporting
confidence: 79%
See 3 more Smart Citations
“…miR-96 and miR-200 families are known to suppress neural differentiation by targeting key neural transcription factors PAX6 and ZEB1 [36]. Consistent with their upregulation (Supplementary information, Table S5), we observed that pax6 and zeb1 mRNAs were significantly downregulated in ADAR1 KD H9 cells upon differentiation (data not shown).…”
Section: Catalytically Inactive Adar1-e912a Rescues Retarded Neural Isupporting
confidence: 79%
“…At 10 and 17 days of neural differentiation, hESC-derived primitive and definitive neuroepthelial (NE) cells with scramble shRNA treatment presented typical columnar NE morphology and were organized into rosettes [36][37][38] (Figure 1D and 1E), similar to the structure of NE cells from WT hESC induction (as discussed below and data not shown). Noticeably, although differentiating hESCs with stable ADAR1 knockdown also formed rosette-like structures, these cells expressed low levels of PAX6, SOX1 and FOXG1 ( Figure 1D and Supplementary information, Table S1), and formed much Table S1.…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 71%
See 2 more Smart Citations
“…Finally, in this study we have demonstrated for the first time that miRNA-200c-ZEB1 axis is a critical regulator for chick embryonic blood vessel formation by in vivo inhibition of miRNA-200C or −150 in developing chick embryos. In the meantime, other researchers also reported that miR-200c promotes mesodermal specification while repressing neuroectodermal differentiation from ESCs [95], suggesting that miR-200c may play a cell-autonomous role in mediating EC differentiation from stem cells. Interestingly, miR-200b displays an antiangiogenic activity in tumor and in embryonic vascular development [96,97], partially through repressing the crucial endothelial lineage related transcription factor E26 oncogene homolog 1 (Ets-1) [98].…”
Section: Mir-200 Familymentioning
confidence: 95%